Association of employment status and income with self-rated health among waged workers with disabilities in South Korea: population-based panel study - Choi, Jae Woo; Kim, Juyeong; Han, Euna; Kim, Tae Hyun (BMJ open, 2019)
ObjectiveThis study aimed to examine the association of employment status and income with self-rated health among waged workers with disabilities in South Korea.MethodsThis study used the Panel Survey of Employment for the Disabled from 2011 to 2015. A total of 951 waged workers with disabilities were selected as baseline subjects in 2011 and were followed up for 5 years. This study used a generalised linear mixed model after adjusting for covariates.ResultsAmong 951 waged workers with disabilities, the results showed that 39.3% of workers with disabilities reported poor self-rated health. Workers with disabilities with a precarious employment status and lower income were 1.22 (95% CI 1.21 to 1.23) and 1.81 (95% CI 1.80 to 1.83) times more likely to have poor self-rated health than those with permanent employment and higher income, respectively. A subgroup analysis found that precarious workers with disabilities in lower income households had higher possibilities of poor self-rated health.ConclusionThis study suggests that precarious employment and lower income of waged workers with disabilities are significantly associated with poor self-rated health compared with those with permanent jobs or higher income.